Comparison of back muscle and leg muscle strength among different groups of female medical students (Bangladesh Medical Journal Khulna, 2022)
Background: Muscle strength is the ability of a muscle or muscle group to exert force. Good muscle strength increases physical performance and may be important in weight maintenance.Objective: The present study aimed at comparing the back muscle and leg muscle strength among different groups of female medical students which might be used as base-line findings for other similar sedentary professionals.Methods: A cross-sectional analytical study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from January 2016 to December 2016. The study was performed on 118 female Bangladeshi medical students. It was conducted on three groups depending on body mass index- normal group, overweight group and obese group.Results: Significant difference of mean back muscle and leg muscle strength was observed among normal, overweight and obese groups. The mean back muscle and leg muscle strength were higher in normal group than overweight group and lower in obese group. Significant difference (p=0.030) was observed between mean leg muscle strength of over-weight and obese group.Conclusion: The results of the present study demonstrate that back muscle and leg muscle strength were significantly higher in normal group than overweight group and it is lower in obese group.Bang Med J Khulna 2021; 54 : 17-20